An extended car-following model considering multi-anticipative average velocity effect under V2V environment - Kuang, Hua; Wang, Mei-Ting; Lu, Fang-Hua; Bai, Ke-Zhao; Li, Xing-Li (Physica A, 2019)
Vehicle-to-vehicle (for short, V2V) communication technology is regarded as a promising technology to improve traffic efficiency and safety. In this paper, an extended car-following model is proposed to simulate traffic flow by considering multi-anticipative average velocity effect (including the average velocity and the mean expected velocity field effect of preceding vehicles group) under V2V environment. The stability condition of this model is obtained by applying the linear stability theory. The phase diagram comparison and analysis shows that the multi-anticipative average velocity effect can effectively enhance the stabilization of traffic system. In particular, the average velocity effect plays a more important role than that of the mean expected velocity field effect in improving the stability of traffic flow. The mKdV equation is derived to describe the evolution characteristics of traffic density waves by using the reductive perturbation method. Furthermore, the numerical simulation is carried out to validate the theoretical results, and indicates that the traffic jam can be suppressed efficiently via taking into account multi-anticipative average velocity effect. •A new car-following model considering multi-anticipative average velocity effect is presented.•Linear analysis is carried out to study the stability of traffic flow.•The mKdV equation is derived from nonlinear analysis to describe the density wave of traffic jam.•The effect of multi-anticipative average velocity can effectively improve the stability of traffic flow.